Drug Error beyond the Hospital and Role of Pharmacists in drug Safety Process - Khan, Gulam Muhammad (Janapriya Journal of Interdisciplinary Studies, 2019)
Medication related error is one of the most common error prevailing in this time. Medication error can be defined as a ‘failure in the treatment process that leads to or has potential to lead to harm to the patient. Medication error can occur from the process of ordering to the administration to the patient. Among the healthcare professionals; a pharmacist can be responsible in identification of contributing factors and reducing its occurrence. Great efforts are needed in this area, due to diversity in the types of errors, the relationship between the provider and the patient, information transfer, optimization of e-prescribing systems, the lack of adequate training in analyzing the collected data and poor practical strategies for maintaining accurate drug lists in electronic medical records. Recently healthcare professionals have started becoming aware about the risks of patients’ medication exposure. After all, still the area of medication safety beyond the hospital setting needs community pharmacy intervention to avoid malpractice claims and misled decisions in solving medication safety-related problems in the outpatient setting. Approaches like medication reviews and reconciliation, monitoring drug therapy, reporting error will help in identify and prompt the detection of errors, open productive discussions, quality control checks, and effective system-based decisions like performing risk assessment subsequently reduces the harm and risks before patient is exposed to any form of drug error.